Goniasteridae Forbes 1841 - Mah, Christopher L. (Zenodo, 2016)
GONIASTERIDAE Forbes 1841 Taxonomic conventions in this paper follow those of Mah (2014b) including changes indicated by the molecular revision of the Valvatacea (Mah & Foltz 2011) which separate Pseudarchaster and the “pseudarchasterines” from the Goniasteridae. This is a classification which is also consistent with morphology-based cladistics (Blake 1987). Full taxonomic descriptions for relevant hippasterines ( Evoplosoma and Hippasteria ) are reported in detail by Mah et al. (2010, 2014). For the sake of completeness, these taxa are included in the key and summarized briefly below by occurrence and other summary information. The checklist below highlights all Goniasteridae with known occurrence below 1000 meter depths from the west coast of North America. Those species with an (*) are new records which are described or noted herein. Two species, Nymphaster diomedeae and Litonotaster tumidus , both described by Ludwig (1905) from more southern regions closer to the Baja and Central California and have not been encountered in the North Pacific. However some deep-sea species described by Ludwig (1905), such as Pentagonaster (= Pillsburiaster) ernesti and Mediaster (= Bathyceramaster n. gen. ) elegans were previously known only from the tropical East Pacific (off Baja and Central America, etc.) but have since been found farther north (as outlined below). Based on these further range extensions and the sometimes wide-ranging occurrence of lower-bathyal/abyssal species, these two species were included as a contingency, even though new records are not reported. One included genus, Sibogaster includes two species with occurrence beyond the geographic limits of the current treatment with data for specimens in the central Tropical Pacific and the North Atlantic. Although all species are included in the identification key and taxonomic summary, emphasis is placed on those taxa for which new information is available. Although all species are included in the identification key and taxonomic summary, not all taxa are ...